The Interpretation of Sundanese Educational Philosophy in Traditional Idiomatic Expressions - Sudaryat, Yayat (EDUCARE, 2014)
ABSTRACT: The study was aimed at exposing the result of reinterpretation and reformulation of Sundanese educational philosophy in traditional idiomatic expressions. Traditional idiomatic expressions are plastic-aesthetic words having connotative meanings. The structures and sounds of words in traditional idiomatic expressions do not change from one generation to another. This study applied descriptive method. Bibliographic study, intuition, elicitation, and questionnaires were used to get data. The data were, then, analyzed using hermeneutic method by immediate constituent analysis. This study found that traditional idiomatic expressions implied high moral values and reflected local wisdom, particularly those dealing with character building. Philosophically, character building or education process involved education trident or three education practice, i.e. planning, implementation, and evaluation. Besides, the values of Sundanese education practice consisted of the objective, methodology, teachers and students, media and learning materials, and evaluation. Education should start as early as possible, so that the result could be gained when one reached his or her adulthood (âkudu guguru ti lelembut, diajar ti bubudak, geus gede kari makenaâ). The teachers and students should be caring and attentive (âsilih asah, silih asih, silih asuhâ). Thus, it would create âjelema masagiâ (complete people) who were well-rounded; and âlegok tapak genteng kadekâ (had a lot of experiences), and âcageur, bageur, bener, pinter, singer, tur panggerâ (had the qualities of being healthy, morally-right, intellectual, skillful, and tough). KEY WORDS: Philosophy of education, traditional idiomatic expressions, Sundanese character, local wisdom, Nusantara languages, unity in diversity, and Indonesia nation-state.About the Author: Dr. Yayat Sudaryat is a Senior Lecturer at the Department of Sundanese Language Education, Faculty of Language and Art Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. E-mail: kisudaryat_sunda@yahoo.comHow to cite this article? Sudaryat, Yayat. (2014). âThe Interpretation of Sundanese Educational Philosophy in Traditional Idiomatic Expressionsâ in EDUCARE: International Journal for Educational Studies, Vol.6(2) February, pp.119-128. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 17, 2013); Revised (January 19, 2014); and Published (February 17, 2014).Â  Â